Effect of Sodium Hydroxide Pretreatment of NiOx Cathodes on the Performance of Squaraine‐Sensitized p‐Type Dye‐Sensitized Solar Cells. Issue 4 (25th January 2018) - Bonomo, Matteo; Magistris, Claudio; Buscaino, Roberto; Fin, Andrea; Barolo, Claudia; Dini, Danilo
Abstract: Squaraines are full‐organic dyes employed as sensitizers in p ‐type dye‐sensitized solar cells ( p ‐DSSC). Their absorption spectrum shows a wide tunability that ranges from visible to NIR. Sensitization in the NIR region is crucial for exploiting a particularly intense portion of the solar spectrum. In this work three squaraines will be presented and tested as sensitizers in NiO‐based p ‐type DSSCO4_C2, O4_C4 andO4_C12 ). The structures of the dyes differ for the length of the alkyl side chain (C2, C4 and C12). Alkyl side chains improve the solubility of the dye, influence the extent of dye loading on the electrode and affect the overall efficiency of devices. The generally low stability of squaraines represents a critical issue in view of their employment as sensitizers of p ‐DSSC. Such a problem becomes even more evident when this class of molecules is bound onto an acidic surface like the one of the photocathode here employed: non‐stoichiometric nickel oxide (NiOx ). NiOx possesses a quite acidic character because of the high surface concentration of Ni(III) sites. To buffer the surface acidity of NiOx due to the presence of high‐valence states of nickel, we considered the electrode pretreatment with sodium hydroxide (NaOH) prior to sensitization. This assures a major stability of the solar cell. At the same time the chemisorbed hydroxyl moieties act as passivating agents of the Ni(III) sites thus diminishing the surface concentration of sites for dye anchoring. Abstract : J−V curves of treated (dotted line) and untreated (solid line) electrode with different squarainic sensitizers. The effect of soda pretreatment is to reduce the overall efficiency because of the adsorption competition between hydroxyl moiety of soda and carboxylic group of the sensitizers. Nevertheless, NaOH pretreatment enhance the long term stability of the devices (ISO−D1, more than 60 days) no matter the sensitizer employed.